Trends and Impacts of Virtual Reality and E-Mobility Integration in Vocational Education and Training - Arif Bintoro Johan; Samsul Hadi; Nurcholish Arifin Handoyono; Krida Singgih Kuncoro; Dhimas Nur Setyawan; Devi Septiani; Fitria Sulistyowati; Betty Kusumaningrum; Sony Yunior Erlangga (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
This bibliometric study analyzed 309 Scopus-indexed documents (2007–2026) to examine research trends integrating Virtual Reality (VR), electric bicycle conversion, and vocational education. The study used a bibliometric approach to map scientific developments at the intersection of VR, e-mobility, and vocational education. Findings indicate that this field is rapidly developing, with an annual growth rate of 3.72% and a very young average document age (2.08 years). China, India, and the United States dominate publications, while Europe leads in international collaboration. Through thematic mapping, VR was identified as a key link bridging sustainability, transportation safety, and smart city technology. VR and electric vehicle development were among the Basic Themes, while transportation safety emerged as a Motor Theme with strong momentum. However, the analysis revealed a critical gap: the lack of engagement with vocational education and e-learning topics. The lack of exploration of VR as a training tool for electric bicycle conversion in vocational high schools suggests a broad research opportunity. This study emphasizes the importance of integrating immersive simulation and competency-based learning to prepare a skilled workforce in the future sustainable transportation sector.